The ground pattern of midgut structure in Julidae (Julida: Juloidea): a study on selected species - Magdalena Rost-Roszkowska; Łukasz Chajec; Dalibor Stojanović; Dragan Antić (Arthropod Systematics & Phylogeny)
The middle endodermal region of the digestive system (midgut) of arthropods is responsible for processes related to digestion but is also considered an organ participating in homeostasis maintenance. Therefore, many experimental studies, for example, related to the effect of various stressors on the organism, are conducted on the epithelium of this intestine. However, it is important to know the basic structure and ultrastructure of the midgut tissues. In myriapods (e.g., millipedes), the midgut has the form of a simple tube lined with a single layer of epithelium, surrounded by hepatic cells and visceral muscles. Considering the fact that millipedes can inhabit various terrestrial environments, feed on a variety of foods, and are important links in food chains, they can be considered good models for ecotoxicological studies. Thus, we selected eight species belonging to the family Julidae (order Julida) to investigate whether any distinct ground pattern for this organ appears within one millipede systematic group and whether it is possible to translate it into the general pattern of the midgut epithelium in millipedes: Leptoiulus sarajevensis (Verhoeff, 1898), Leptoiulus trilineatus (C. L. Koch, 1847), Cylindroiulus boleti (C. L. Koch, 1847), Megaphyllum bosniense (Verhoeff, 1897), Pachyiulus cattarensis (Latzel, 1884) and Pachyiulus hungaricus (Karsch, 1881) as representatives of the epigean fauna as well as Leucogeorgia longipes Verhoeff, 1930 and Leucogeorgia gioi Antić and Reip, 2020 as true cave-dwelling species. The study was performed using light and transmission electron microscopy. The results revealed a general pattern of all cells forming the midgut epithelium in Julidae, as well as the hepatic cells surrounding the midgut. Some small differences were observed, which are probably related to the type of food consumed.